2012
DOI: 10.1001/archpediatrics.2011.1900
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perceptions of Toddler Body Size

Abstract: Objectives: To examine (1) accuracy of maternal perceptions of toddler body size; (2) factors associated with accuracy of toddler body size; and (3) how maternal satisfaction relates to accuracy/toddler body size. Design: Cross-sectional. Setting: Low-income community sample from suburban Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)/urban pediatric clinics. Participants: Two hundred eighty-one mother-toddler dyads (toddlers: 54.1% male; mean age, 20.2 months; 70.8% Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 29 publications
2
37
2
2
Order By: Relevance
“…In a world of rising childhood obesity, perpetrating a need for weight gain among healthy children who are below the 25th percentile in weight-for-height is potentially harmful. This marketing strategy plays on well-documented perception errors of mothers regarding their children’s size [95] and is likely to exacerbate rather than alleviate the global child overweight and obesity trend. …”
Section: Feeding Obesitymentioning
confidence: 99%
“…In a world of rising childhood obesity, perpetrating a need for weight gain among healthy children who are below the 25th percentile in weight-for-height is potentially harmful. This marketing strategy plays on well-documented perception errors of mothers regarding their children’s size [95] and is likely to exacerbate rather than alleviate the global child overweight and obesity trend. …”
Section: Feeding Obesitymentioning
confidence: 99%
“…The perceived risk of early childhood obesity is a central component because of prevailing beliefs about larger infants being healthier or better [48, 61, 62], tendencies to practice unresponsive feeding such as pressuring, despite acknowledging infant satiety cues [63, 64], failure to perceive overweight children as overweight [62, 65], and a general belief that young children will grow out of any early overweight or obese status [61, 66]. …”
Section: Resultsmentioning
confidence: 99%
“…(9) Mothers demonstrated knowledge about the representation of a "child with normal weight," although their statements demonstrate a distance from this concept This was identified in other studies which observed no correlation between visual and verbal maternal perception in the classification of their children's weight, especially when they were overweight or obese (14) and the imprecision in maternal perception when assessing their overweight child, and also highlighting their satisfaction with the child's excess weight. (15) The opposite can also be ascertained when the mothers whose children were underweight, showed dissatisfaction for believing that their children were outside a standard image and weight expected for their age group. (15) Although none of the children in this study can be classified as obese, four mothers underestimated their children's weight, classifying them with appropriate weight, even though they were at risk of overweight/overweight.…”
Section: Discussionmentioning
confidence: 99%
“…(15) The opposite can also be ascertained when the mothers whose children were underweight, showed dissatisfaction for believing that their children were outside a standard image and weight expected for their age group. (15) Although none of the children in this study can be classified as obese, four mothers underestimated their children's weight, classifying them with appropriate weight, even though they were at risk of overweight/overweight. These results are similar to the findings of another study, which found out that parents did not perceive overweight or obesity in their children.…”
Section: Discussionmentioning
confidence: 99%